2005
DOI: 10.1056/nejmsa043266
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Treatment of Mental Disorders, 1990 to 2003

Abstract: Background-Although the 1990s saw enormous change in the US mental health care system, little is known about changes in prevalence or treatment of mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

58
1,103
5
29

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 1,740 publications
(1,216 citation statements)
references
References 28 publications
(19 reference statements)
58
1,103
5
29
Order By: Relevance
“…These disorders are a leading cause of disability globally (Steel et al, 2014). It is estimated that less than one-third of individuals in the USA and Europe and less than one-fifth in low- and middle-income countries (LMICs) receive treatment for treatable psychiatric conditions (Group, 2007; Kessler et al, 2005; Wang et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…These disorders are a leading cause of disability globally (Steel et al, 2014). It is estimated that less than one-third of individuals in the USA and Europe and less than one-fifth in low- and middle-income countries (LMICs) receive treatment for treatable psychiatric conditions (Group, 2007; Kessler et al, 2005; Wang et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that undiagnosed mental illness (particularly among men and certain ethnic subgroups), lack of insurance, and low income may be predictors of the underuse of antidepressants and other mental health treatment modalities (11,14,20,23–27,3032). We fit a multivariate logistic regression model to examine predictors of overuse, including age, gender, self-reported race-ethnicity, education level, income group, and insurance status (11,14,20,23–27,31,32).…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiologic surveys have been used to bound estimates of overuse of mental health treatments. Results suggest that approximately half of respondents who obtained treatment for mental or substance use disorders in a study year did not meet criteria for any disorders assessed (23,28,29). Recent analyses suggest that these overuse estimates are likely biased upward (11).…”
mentioning
confidence: 95%
See 2 more Smart Citations